Harmful Traditional Practices of Umbilical Cord in Edaga Hamus Community, Asmara, Eritrea - Negash FB; Simel LL; Tekle LR; Berhane BB (Dove Medical Press, 2024)
Feven Beletse Negash,1 Laban Lebahati Simel,2 Luwam Russom Tekle,1 Betiel Biniam Berhane3 1Public Health, Ministry of Health, Asmara, Eritrea; 2Community Medicine and Primary Health Care, Orotta College of Medicine and Health Sciences, Asmara, Eritrea; 3Eritrea Institute of Technology, College of Science, Department of Biology, Mainefhi, EritreaCorrespondence: Feven Beletse Negash, Tel +2917722712, Email beletsefeven21@gmail.comPurpose: Globally, the cord care practices contribute to neonatal infections and account for a large proportion of neonatal deaths annually, especially in low-income countries. This study has been provoked by the absence of previous similar research in this locality. The study aimed at exploring and highlighting the factors and practices in the community that influence umbilical cord care to identify the areas of intervention.Methods: This was a cross-sectional study conducted among mothers of neonates in Edaga Hamus community who had given birth a month prior to the study. The research team prepared a questionnaire used for data collection on a face-to-face interview, which lasted for 15 minutes for each participant. SPSS version 22 was used for quantitative analyses. Descriptive statistics were presented in frequencies and percentages, and bivariate correlations were used to analyze the association between independent and dependent variables.Results: One hundred and seventy-five women participated in this study, with an age range of (19 to 43) years (28.5 ± 5.1 years) of whom (84.5%) used the dry care method, whereas (19%) of the total cord infections were related to different traditional practices. A higher proportion of women (90%) expressed fear and depression once the cord became infected. A greater number of women followed the advice given by nurses, and this finding was significant (p value = 0.008).Conclusion: Majority of the participants in this study acknowledged the importance of using the dry care method as recommended by World Health Organization. Those neonates whose cords were exposed to unwarranted practices had delayed detachment. This study confirmed that health promotion in cord care practices should involve family members and the community to achieve successful outcomes.Keywords: cord care, neonate, newborn, practices